Meglumine Sodium Succinate in Diabetic Ketoacidosis - M. I. Neimark; E. A. Kloster; A. A. Bulganin; A. V. Ioshhenko; E. A. Subbotin (Общая реаниматология)
The most common agent used for infusion therapy in patients with diabetic ketoacidosis (DKA) is isotonic 0.9% sodium chloride solution. However, infusion of required volumes can result in development of iatrogenic complications — i. e., worsening of metabolic hyperchloremic acidosis in DKA patients with already altered acid-base balance. Balanced crystalloid solutions can be used as alternative to saline.Objective. To evaluate the feasibility of using meglumine sodium succinate (MSS) balanced crystalloid solution in DKA.Material and methods. We examined 2 groups of patients, 30 subjects each, with moderate and severe diabetic ketoacidosis admitted to anesthesiology and intensive care unit. Patients from both groups were administered with insulin and an infusion therapy was employed according to current clinical guidelines for the management of patients with complications of diabetes mellitus. In the comparison group, infusion therapy included 0.9% sodium chloride, 4% potassium chloride, and 5% dextrose. In the study group MSS intravenous drip infusions 10 ml/kg/daily were added to the infusion protocol. Volumes and infusion rates were comparable in both groups. The following indicators were evaluated: time to resolution and DKA resolution rates during thorough monitoring (first 48 hours of therapy), the time (in hours) before discontinuation of insulin infusion; the time to complete consciousness recovery (15 items on the Glasgow Coma scale); the duration (in hours) of stay in the intensive care unit (ICU), dynamics of blood electrolytes; parameters of acid-base balance; levels of glycemia and lactatemia.Results. All patients improved and were transferred from ICU, the mortality rate was 0%. Infusion of MSS shortened the time to DKA resolution (30.0 h [24.0 h; 36.0 h] in the study group, vs 44.5 h [36.5 h; 51.5 h] in the comparison group (P=0.001)); DKA resolution rates during 48 hours from initiation of therapy achieved 90.0% (27) in the study group, vs 66.7% (20) in the comparison group (P=0.060)); duration of intravenous insulin infusion was 32.0 h [24.5 h; 40.0 h] in the study group vs 48.0 h [40.0 h; 55.5 h] in the comparison group (P=0.001)); duration of ICU stay was 41.0 h [30.0 h; 48.0 h] in the study group, vs 56.0 h [50.0 h; 66.3 h] in the comparison group (P=0.001).Conclusion. Infusion of a balanced succinate-containing crystalloid solution improves the results of DKA treatment, as compared to traditional infusion of 0.9% sodium chloride.